Global Logistics and Supply Chain Strategies for the 2020s Vital Skills for the Next Generation - Merkert, Rico.; Hoberg, Kai. (Cham : Springer International Publishing : Imprint: Springer, 2023)
Logistics and supply chain management is facing disruptive economic, technological and climate change developments that require new strategies. New technologies such as the Internet-of-Things, digital manufacturing or blockchain are emerging quickly and could provide competitive advantage to those companies that leverage the technologies smartly while managers that do not adopt and embrace change could be left behind. Last but perhaps most important for mankind, sustainability aspects such as low-carbon transportation, closed loop supply chains or socially-responsible supply chain setups will become essential to operate successfully in the future. All these aspects will affect logistics and supply chains as a whole as well as different functional areas such as air cargo, maritime logistics or sourcing/procurement. This book aims to dive into several of these functional topics to highlight the key developments in the next decade predicted by leading global experts in the field. It features contributions and key insights of globally leading scholars and senior industry experts. Their forward-looking perspectives on the anticipated trends are aimed at informing the reader about how logistics and supply chain management will evolve in the next decade and which academic qualities and skills will be required to succeed in the "new normal" environment that will be characterized by volatile and increasingly disrupted business eco-systems. Future scenarios are envisaged to provide both practitioners and students with insights that will help them to adapt and succeed in a fast changing world.
Chapter 1. The Future of Logistics and Supply Chain Management: Changing Skill Sets and Smart Career Choices -- Chapter 2. The Impact on Supply Chain Networks of Shifting Demand and Supply Dynamics -- Chapter 3. AI in Logistics and Supply Chain Management -- Chapter 4. How to Design Human-machine Interaction in Next-generation Supply Chain Planning -- Chapter 5. The Circular Economy and Green Supply Chains -- Chapter 6. Preparing Logistics for the Low Carbon Economy -- Chapter 7. The Future of 3PLs -- Chapter 8. Air Cargo Logistics - The Dawning of a Golden Decade? -- Chapter 9. Maritime Logistics for the Next Decade - Challenges, Opportunities and Required Skills -- Chapter 10. Future Directions in City Logistics -- Chapter 11. Recent Advances of Service Supply Chain Management -- Chapter 12. Competence Development, Learning and Change in Supply Chain Management -- Chapter 13. Startups in the Logistics Sector: Value Propositions and Potential Impact -- Chapter 14. Warehousing 2030 -- Chapter 15. Future of Procurement - Insights from a Global Survey -- Chapter 16. Agility in Supply Chain Planning and Execution -- Chapter 17. Risk Driven Supply Chain Design - Options and Trade-offs in Complex Environments -- Chapter 18. Supply Chain Transparency Using Blockchain: Benefits, Challenges, and Examples -- Chapter 19. The Potential of Blockchain in SCM - PI Meets Blockchain -- Chapter 20. Collaboration in Humanitarian Operations in the Context of the COVID-19 Pandemic -- Chapter 21. Logistics Challenges and Opportunities in Africa in the 2020s.
Keywords: Production management; Operations research; Management science; Industrial engineering; Production engineering; Operations Management; Operations Research, Management Science .; Industrial and Production Engineering